2016
DOI: 10.1016/j.colsurfa.2016.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Urea-based gemini surfactants: Synthesis, aggregation behaviour and biological activity

Abstract: with the maximum antimicrobial activity found at the spacer length of 6 CH2 groups for bacteria and 8 CH2 groups for fungi. This is related to a different composition of cell membrane of the used microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…A similar observation was also made in our previous study of aggregation of urea-based gemini surfactants [31] where nonlinear dependences of aggregation parameters were found as a function of the spacer length with worse aggregation detected for medium spacer lengths. Moreover, strong aggregation for short spacer gemini molecules with urea groups in the alkyl chains also resulted from the increased hydrogen bonding between urea groups [31]. This could also be the case of gemini molecules with short spacer ( a1, a2 ) where the amide groups in the spacer are separated by just one or two methylene groups and intramolecular hydrogen bonding can take place which results in the increased aggregation number values (Figure 1 and Figure 2A).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A similar observation was also made in our previous study of aggregation of urea-based gemini surfactants [31] where nonlinear dependences of aggregation parameters were found as a function of the spacer length with worse aggregation detected for medium spacer lengths. Moreover, strong aggregation for short spacer gemini molecules with urea groups in the alkyl chains also resulted from the increased hydrogen bonding between urea groups [31]. This could also be the case of gemini molecules with short spacer ( a1, a2 ) where the amide groups in the spacer are separated by just one or two methylene groups and intramolecular hydrogen bonding can take place which results in the increased aggregation number values (Figure 1 and Figure 2A).…”
Section: Resultssupporting
confidence: 87%
“…This results in the formation of small spherical micelles with small hydrodynamic diameter, small aggregation numbers independent of surfactant concentration and large interfacial area per surfactant molecule [29,30]. A similar observation was also made in our previous study of aggregation of urea-based gemini surfactants [31] where nonlinear dependences of aggregation parameters were found as a function of the spacer length with worse aggregation detected for medium spacer lengths. Moreover, strong aggregation for short spacer gemini molecules with urea groups in the alkyl chains also resulted from the increased hydrogen bonding between urea groups [31].…”
Section: Resultssupporting
confidence: 76%
“…The reason for this may be that policationic compounds can easily interact with charged cell surfaces. Moreover, they can increase membrane fluidity and consequently lead to cell death [ 32 , 33 , 34 , 35 ]. The results presented in our study are similar to those reported for yeast by Obłąk et al [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analytical, Inorganic, Organic, Physical, Materials Science microorganisms as microbial colloids (Peng et al 2018;Pisarcik et al 2016). It's worth noting that microbial colloids are neither mineral colloids nor soil humus colloids.…”
Section: Chemistry Journalsmentioning
confidence: 99%